2002
DOI: 10.1002/jclp.10049
|View full text |Cite
|
Sign up to set email alerts
|

Just say no to psychotropic drugs!

Abstract: Prescribing drugs for mental disorders by psychologists means accepting an invalid model--the brain disease, biological-defect explanation of psychopathology--that is advanced by political conservatives and accepted by some naive, well-intentioned, but misinformed moderates who have not thought critically about the issue. Conservative psychiatry serves the ruling class by rejecting or ignoring the fact that most mental disorders are learned in the context of social and economic injustice, and familiar dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…The societal need perspective on PPP was addressed in Albee's (2002) paper "Just Say No to Psychotropic Drugs!" and Norfleet's (2002) paper "Responding to Society's Needs: Prescription Privileges for Psychologists."…”
Section: Societal Need For Pppmentioning
confidence: 40%
See 3 more Smart Citations
“…The societal need perspective on PPP was addressed in Albee's (2002) paper "Just Say No to Psychotropic Drugs!" and Norfleet's (2002) paper "Responding to Society's Needs: Prescription Privileges for Psychologists."…”
Section: Societal Need For Pppmentioning
confidence: 40%
“…Norfleet also raised a critical question of how applied psychologists can survive economically. While her solution for economic survival is PPP, other articles in this special series offer alternative ways applied psychologists can make a living (Albee, 2002;McFall, 2002;and Hayes et al, 2002). Albee (2002) argued that the role of psychology in society addresses different human needs than does the role of medicine, and that these disciplinary boundaries are important to maintain.…”
Section: Societal Need For Pppmentioning
confidence: 41%
See 2 more Smart Citations
“…The RÂP proposal remains controversial within psychology and objections involve anticipated negative effects of the amount of training (Albee, 2002;Bush, 2002;Hayes & Heiby, 1996, 1998Hayes, Walser, & Bach, 2002;Heiby, 2002;Heiby et al, 2004;McFall, 2002;Pollitt, 2003;Sechrest & Coan, 2002;Wagner, 2002). Proponents of RÂP have observed that the major reason for the failure of most enabling legislation is concern over the quality of the APA model training (Fox et al, 2009), and the consumer protection reasons given in one governor's veto of an enabling bill supports this impression (Lingle, 2007).…”
Section: Context Of Evaluating Râp Trainingmentioning
confidence: 42%